School Principal Leadership in Developing Non-Academic Student Achievements: Adaptive Strategies in Resource-Constrained Contexts - Kurniadiningsih, Rosalia Sitowati; Miftahuddin, Miftahuddin; Bustari, Meilina (Papanda Publisher, 2025)
In the era of globalization and rapid technological development, holistic education balancing academic and non-academic achievements has become essential for developing 21st-century learners. However, many schools, particularly in remote areas, struggle to develop students' non-academic potential due to various constraints. This study analyzed the challenges, strategies, and impacts of school principal leadership in improving students' non-academic achievements at SMAN 2 Merauke and SMAN Plus Urum in Merauke Regency, Indonesia. A qualitative descriptive approach was employed, with data collected through semi-structured interviews, non-participatory observations, and documentary analysis. Participants included school principals, vice principals, teachers, students, and school committee representatives from both institutions. Data were analyzed using the Miles, Huberman, and Saldaña model, with credibility maintained through source and method triangulation. Findings revealed that both schools faced multidimensional challenges including human resource limitations, inadequate facilities and infrastructure, budget constraints, low student participation, and minimal external support. Challenges were substantially more severe at SMAN Plus Urum due to its remote location. Principals implemented adaptive strategies including internal capacity building through peer learning and student mentorship, creative facility optimization, selective activity prioritization with transparent budget management, recognition-based motivation systems, and gradual community engagement. These strategies generated positive impacts on teacher professional development, student character formation (confidence, discipline, resilience), enhanced school reputation, and emerging community support for holistic education. Effective leadership in resource-constrained contexts requires adaptive, creative, and collaborative approaches that maximize existing capabilities while gradually building external support networks. The study contributes to understanding educational leadership in developing country contexts and provides practical insights for principals facing similar challenges.